2010
DOI: 10.1111/j.1365-2559.2010.03621.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bcl‐2 family proteins and association with clinicopathological characteristics of oral squamous cell carcinoma

Abstract: Our results showed the involvement of the Bcl-2 family of proteins in OSCC tumorigenesis and suggest that the expression of apoptotic molecules might be used as a prognostic indicator for OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…On the contrary to previous reports Coutinho-Camillo et al, found that expression of Bcl-2 in HNSCC was not significantly associated with any of the clinicopathological parameters. This difference in results could be explained by the large number of cases (229) included in their study [58].…”
Section: Archives In Cancer Research Issn 2254-6081mentioning
confidence: 84%
“…On the contrary to previous reports Coutinho-Camillo et al, found that expression of Bcl-2 in HNSCC was not significantly associated with any of the clinicopathological parameters. This difference in results could be explained by the large number of cases (229) included in their study [58].…”
Section: Archives In Cancer Research Issn 2254-6081mentioning
confidence: 84%
“…Alterations in the expression levels of apoptosis-related proteins have been reported in several cancers, including oral cancer [14][15][16]. In this study, by tissue microarray (TMA) analysis of 229 oral squamous cell carcinoma (OSCC) cases, the expression profiles of 23 apoptotic proteins were examined and a hierarchical cluster analysis was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the expression of 23 proteins, our group have demonstrated that decreased expression of caspase-3 correlates with lymph node metastasis, lower caspase-7 levels are associated with disease-free survival in oral cancer, high Bim-Long expression is linked to overall survival and that elevated PUMA levels are associated with disease-free survival in oral cancer patients [15,16]. Elevated expression of Apaf-1 and survivin is associated with the absence of embolization, and the expression of Smac/DIABLO and cytochrome c is not significantly associated to any clinicopathological characteristic (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations